Optimizing the in vitro production of immunomodulatory cells for the induction of tolerance in solid organ transplantation - Nils Ågren; Ming Yao; Carl Skantze; Keyvan Habibi; Bo-Göran Ericzon; Makiko Kumagai-Braesch (PLoS ONE, 2025)
Background Cell therapy can be utilized to induce operational tolerance following solid organ transplantation. In thi study, donor-specific immunomodulatory cells (DSIMC) are generated by co-culturing recipient peripheral blood mononuclear cells (PBMC) with irradiated donor PBMC in the presence of belatacept, a CTLA-4-IgG1 fusion protein. DSIMC promote a regulatory response to donor cells. Reinfusion of these cells into the recipient may induce donor-specific tolerance, enabling weaning or complete cessation of immunosuppression (IS). Aim This study aims to determine optimal culture conditions for DSIMC production. Methods DSIMC were generated by culturing PBMCs from healthy volunteers with irradiated allogeneic PBMC and belatacept. We evaluated the choice of medium, plasma supplementation, costimulation blocker concentration, and red blood cell (RBC) lysis, using automated cell counts, cytokine assays, PCR, and flow cytometry. Results Increasing belatacept concentration (0-80 μg per million cells) resulted in a significant reduction in PD-1 expression in regulatory T cells. RBC lysis reduced inflammatory cytokine production and improved DSIMC generation, as indicated by increased IL-10 and decreased IFN-γ production. Between culture days 9-14, the total cell yield and IFN-γ-producing cell numbers declined, while IL-10-producing cell numbers increased. Conclusion Treating responder and irradiated stimulator PBMC with RBC lysis buffer before co-culture in TexMACS medium supplemented with 1% autologous plasma and 40 μg belatacept per million cells for 14 days produces DSIMC which meet established quality criteria. The protocol is currently currently under evaluation in a clinical study.